2022
DOI: 10.1073/pnas.2116127119
|View full text |Cite
|
Sign up to set email alerts
|

A molecular interpretation of the toughness of multiple network elastomers at high temperature

Abstract: Significance Soft materials can be toughened by creating dissipative mechanisms in stretchy matrixes. Yet using them over a wide range of temperatures requires dissipative mechanisms independent of stretch rate or temperature. We show that sacrificial covalent bonds in multiple network elastomers are most useful in toughening elastomers at high temperature and act synergistically with viscoelasticity at lower temperature. We do not attribute this toughening mechanism only to the scission of bonds dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…Visualization of mechanochemical damages in polymeric materials including elastomers and gels is of great significance in both applications and fundamental studies, such as internal damage sensing and fracture mechanism analysis. , The fracture of polymeric materials often couples a wide range of length scales ranging from molecular-scale bond scission (mechanochemical damage), microscale-localized small cracks to macro-crack damage. The polymeric materials are usually designed to be as robust as possible for practical applications, but they are susceptible to catastrophic global failure once the nanoscale mechanochemical damages lead to the microscale-localized cracks, which further percolate to macro-cracks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Visualization of mechanochemical damages in polymeric materials including elastomers and gels is of great significance in both applications and fundamental studies, such as internal damage sensing and fracture mechanism analysis. , The fracture of polymeric materials often couples a wide range of length scales ranging from molecular-scale bond scission (mechanochemical damage), microscale-localized small cracks to macro-crack damage. The polymeric materials are usually designed to be as robust as possible for practical applications, but they are susceptible to catastrophic global failure once the nanoscale mechanochemical damages lead to the microscale-localized cracks, which further percolate to macro-cracks.…”
Section: Introductionmentioning
confidence: 99%
“…Schematic illustrations of the differences between the previously reported methods and the method developed in this work to visualize the mechanochemical damage in polymeric materials. (a) Reported mechanophore method with covalently inserting mechanophores into polymeric materials; , (b) reported mechanoradical polymerization method in which a thermally sensitive polymer PNIPAm is incorporated into the network by mechanoradical-triggered polymerization and is then detected by a fluorescent molecule ANS; reproduced from ref . Copyright 2020 American Chemical Society.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we investigate the regiochemical effects in the mechanochemical retro DA reaction of 9‐π‐extended A‐M DA adducts where the substituent location is varied at the π‐extended phenyl moiety from o ‐ over m ‐ to p ‐substitution (Scheme 1). This popular fluorogenic mechanophore class is being used for the visualization of force‐induced bond scission events in polymer materials due to its excellent photophysical properties 29–35 . While we have implemented structural modifications of the aryl units in 9‐position of the anthracene before, 36–38 the effects of pulling point locations have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Embedded luminescent mechanophores in elastomer networks have confirmed that chains located far from the crack surface (compared to the chain length) become ruptured during crack advance (Boots et al, 2022;Ducrot et al, 2014;Matsuda et al, 2020Matsuda et al, , 2021Slootman et al, 2020), supporting the postulated mechanism of dissipation and toughness enhancement. Unsurprisingly, viscoelastic effects and microscopic dynamics have been found to influence and interplay with the extent of delocalized chain scission measured via luminescent mechanophores (Slootman et al, 2020(Slootman et al, , 2022. Embedded luminescent mechanophores have also been used to visualize delocalized chain scission in elastomer networks undergoing cavitation (Kim et al, 2020;Morelle et al, 2021) and fatigue (Sanoja et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The near-crack dissipation acting in the near-crack zone is Γ tip diss , while the bulk hysteretic dissipation associated with the general process zone is Γ bulk diss . Γ diss is the sum result of these two dissipation contributions: Γ diss = Γ tip diss + Γ bulk diss Slootman et al (2022). has also proposed a similar mechanism governing bond scission in viscoelastic interpenetrating network elastomers.…”
mentioning
confidence: 99%